A quantitative method for assessing resilience of interdependent infrastructures. (January 2017) - Nan, Cen; Sansavini, Giovanni
Abstract: The importance of understanding system resilience and identifying ways to enhance it, especially for interdependent infrastructures our daily life depends on, has been recognized not only by academics, but also by the corporate and public sectors. During recent years, several methods and frameworks have been proposed and developed to explore applicable techniques to assess and analyze system resilience in a comprehensive way. However, they are often tailored to specific disruptive hazards/events, or fail to properly include all the phases such as absorption, adaptation, and recovery. In this paper, a quantitative method for the assessment of the system resilience is proposed. The method consists of two components: an integrated metric for system resilience quantification and a hybrid modeling approach for representing the failure behavior of infrastructure systems. The feasibility and applicability of the proposed method are tested using an electric power supply system as the exemplary infrastructure. Simulation results highlight that the method proves effective in designing, engineering and improving the resilience of infrastructures. Finally, system resilience is proposed as a proxy to quantify the coupling strength between interdependent infrastructures. Highlights: A method for quantifying resilience of interdependent infrastructures is proposed. It combines multi-layer hybrid modeling and a time-dependent resilience metric. The feasibility of the proposed method is tested on the electric power supply system. The method provides insights to decision-makers for strengthening system resilience. Resilience capabilities can be used to engineer interdependencies between subsystems.